3(2x-5)=-x+1

Simple and best practice solution for 3(2x-5)=-x+1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(2x-5)=-x+1 equation:



3(2x-5)=-x+1
We move all terms to the left:
3(2x-5)-(-x+1)=0
We add all the numbers together, and all the variables
3(2x-5)-(-1x+1)=0
We multiply parentheses
6x-(-1x+1)-15=0
We get rid of parentheses
6x+1x-1-15=0
We add all the numbers together, and all the variables
7x-16=0
We move all terms containing x to the left, all other terms to the right
7x=16
x=16/7
x=2+2/7

See similar equations:

| 3(1-3g)=-7+9 | | -6(4+2x)=-52-8x | | 1.3+y/3=-6.2 | | 2(x-6)-4(x-7)=24 | | n=2n−6 | | -1+3f=-7+6f | | 180=90+2x+1+5x+5 | | 99y+100=9 | | 180=90+2x+1+5x+1 | | X+10=-8y;-8y+8=6 | | (X+16)=(4x-20) | | 180=3x+1+2x+4+90 | | .3x=162 | | -9+16g=5g= | | 17x-23=3x+17 | | 5c-6.7.C=2 | | -4x+20-4=12 | | 55x+100=50 | | -6+x/7=-4 | | K^3-4k^2+3k+2=0 | | 5x+5(x+1)=23 | | 7x3=(4x5)+3 | | 12=60x | | a/5+6=4 | | 1/3+7x=10 | | 9x=50+2x+71=90 | | n/5=42 | | -4x-7=-10x+37 | | 29x+99=249 | | 15+.3x=12 | | 5(x+3)=2x+11 | | 2^3x+13=16 |

Equations solver categories